Pretreatment with oral contraceptives benefit POSEIDON group 1 low prognosis patients during GnRH-antagonist protocol: a propensity score-matched retrospective cohort study - Ning Wu; Xin Li; Cheng Zeng; Jing Shang; Xiuli Yang; Qing Xue (Journal of Ovarian Research)
Abstract Background Poor ovarian response (POR) is a challenging condition in assisted reproduction technology. Oral contraceptives (OCs) are commonly used to suppress gonadotropin hormone release in POR patients to synchronize the development of antral follicles before ovarian stimulation. Nevertheless, the question of whether such approach confers advantageous outcomes has elicited inconclusive results in previous studies. Therefore, the objective of this study was to investigate the effect of OCs pretreatment in low prognosis patients stratified by Patient-Oriented Strategies Encompassing Individualized Oocyte Number (POSEIDON) criteria. Methods This retrospective cohort study included 2,222 patients undergoing their first IVF or ICSI cycle from January 2012 to April 2022. After propensity score matching, 369 patients were in the OC pretreatment group and 879 in the control group. Patients were divided into four subgroups based on the POSEIDON criteria. Comparisons of ovarian response and clinical outcomes were conducted, and multivariable logistic regression was used to assess the association between OCs pretreatment and live birth, clinical pregnancy, and pregnancy loss rates. Results Patients in POSEIDON group 1 who received OCs pretreatment exhibited a significant reduction in the dose and duration of gonadotropin administration, along with an increase in the number of oocytes retrieved, 2 pronuclei, available embryos, and good quality embryos, indicating an improvement in their ovarian response to exogenous gonadotropins. Additionally, the live birth rate (P = 0.030) and clinical pregnancy rate (P = 0.012) were significantly higher in the OCs pretreatment group. Multivariate logistic regression analysis demonstrated a positive association between OCs pretreatment and live birth rate (P = 0.008) and clinical pregnancy rate (P = 0.008). However, in POSEIDON group 2 to group 4, there were no significant differences in ovarian response or clinical outcomes between the OCs pretreatment group and the control group. Conclusions Administering OCs as pretreatment prior to ovarian stimulation using gonadotrophin releasing hormone antagonist protocol appears to be a more favorable approach than waiting for natural menses in low prognosis patients belonging to POSEIDON group 1.